O processo justo como fundamento de legitimidade da jurisdição - Marcelo Veiga Franco (2012)
The proposed study was aimed at investigating how the due process constitutes the basis of legitimacy of the judicial function, in order to express the shield of democracy, citizenship and popular sovereignty. To do so, at first, we seek to contextualize the hypothesis versed, through the study of global aspects related to the current judicial crisis. On the assumption that society adopts a contemporary legal culture of litigation, we intend to demonstrate how the mismanagement of public service and managerial court entails ongoing violation of due process. In a second stage of research, attempts to reach a definition of due process appropriate to a democratic state, stemming from the constitutional model of due process. This chapter aims to explain the lack of theories about the nature of the legal proceedings, which were not suited to democracy. At this moment, the definition of what is due process is fundamental. Under the focus of the constitutionalisation of procedural law, the due process of law requires an understanding of the process based on constitutional procedural guarantees, in order to ensure effective and appropriate judicial protection. Set a fair trial, it is proposed the analysis of the foundations of democratic legitimacy of the court, from the constitutional guarantees of the process. In this area, the contradictory, the legal defense, motivation, decision making and judgment naturally, especially, express constitutional guarantees of procedural democracy to justify the exercise of judicial functions, including through the control of adjudicative activity. Finally, we study the process just like an instrument to achieve an appropriate and effective judicial protection. Within the focus of access to fair legal system, it examines how the due process exploits the subjective satisfaction of the substantive right recognized in the sentence and the materialization of the minimum content of fundamental rights, suggesting that in this bias, the application of the theory of integrity Law and the principle of sealing the setback.